Pyrolysis of sawdust in a horizontal tube furnace: Effects of temperature and heating rate on product composition - Selva Kumar Vitiyaa; Lee Zhi Hua; Tan Kok Tat; Sim Jia Huey (E3S Web of Conferences)
The abundant sawdust waste from the timber production industries in Malaysia can be a potential biomass feedstock for pyrolysis process. However, the understanding of product composition and bio-oil quality from sawdust pyrolysis remains limited in Malaysian’s context. In this study, pyrolysis of sawdust was conducted in a horizontal tube furnace to investigate the effects of temperatures (400-550 °C) and heating rates (10-20 °C/min) on the composition of products, quality and properties of bio-oil. According to Gas chromatography (GC) analysis, phenol group appears to be the major compound in the bio-oil. The chemical components of bio-oil were found to be richer at lower reaction temperatures (400-450 °C), where it showcased the presence of phenols, ketones, carboxylic acids, furans, aldehydes, alkenes, alcohols, ether and amine. At increased reaction temperatures (500–550 °C), the process favoured the production of catechol (17%). The yield of bio-char decreased with increasing temperatures and heating rates due to the loss of volatile matter, and 400 °C proved to be the optimum temperature for maximum biochar yield. The biochar also displays porous structure, with increased adsorption capacity. Since the pyrolysis of sawdust could produce phenolic compounds, it appears to be a potential feedstock for biomass pyrolysis.